Chronic Stress Activates PlexinA1/VEGFR2-JAK2-STAT3 in Vascular Endothelial Cells to Promote Angiogenesis - Lu, YanJie; Zhao, HanZheng; Liu, Ying; Zuo, YanZhen; Xu, Qian; Liu, Lei; Li, XiaoMin; Zhu, HongBin; Zhang, Ying; Zhang, Shuling; Zhao, XiangYang; Li, YuHong (Frontiers in Oncology, 2021)
It is known that chronic stress modulates multiple processes in a complex microenvironment, such as angiogenesis and immune function. However, the role of chronic stress inducing tumour angiogenesis and how it contributes to tumour progression are not quite clear. The following study assess psychological state from numerous ambulatory cancer cases (n=332), and chronic stress-related hormone levels were further measured. Here, we show that chronic stress not only causes behavioral changes in human, most importantly attributed to an elevated level of stress-related hormones. To address this, isoprenaline, the agonist of β2-adrenergic receptor (β2-AR), was utilized for simulating chronic stress and demonstrating the mechanism of stress in tumour angiogenesis at molecular level both in vivo and in vitro. As suggested by this study, isoprenaline promote VEGF autocrine of HUVECs, which can induce plexinA1 and VEGFR2 expression. Moreover, we show that isoprenaline promoted the expression of p-JAK2 and p-STAT3 in vitro. The results reveal that, isoprenaline enhances the autocrine of VEGF in HUVECs and up-regulating plexinA1 and VEGFR2 levels, thus activating the phosphorylation of JAK2-STAT3 pathway, the two essential parts during angiogenesis. The present work indicates that, the mechanism of chronic stress in enhancing angiogenesis is probably achieved through activating the plexinA1/VEGFR2-JAK2-STAT3 signal transduction pathway within HUVECs, and this is probably a candidate target for developing a strategy against angiogenesis in cancer.